Differences Between Supplier and Customer Experiences of Marketing Mix in the Construction Industry - Al-Fadly, Ahmad (Frontiers in Built Environment, 2022)
Suppliers often contend they “know” best what the customer wants. Despite using advanced models, such as the 7P (product, place, price, promotion, people, process and physical evidence) marketing mix, competition is right behind. Customers perceive services from their own perspective. This presents a knowledge gap that requires to be filled in an objective way. This research paper elucidates how differences between the supplier perception and the customer perception of delivery are objectively identified. Questionnaires consisting of the 7P marketing mix constructs were created separately for the supplier and the customer. Using a five-point Likert scale, data from 210 supplier staff and 210 customers were collected from the construction industry. Structural Equation Modeling (SEM) established the beta coefficients of latent variables reflecting the perceptions of both the supplier and customer. Both models were tested for internal consistency reliability using Cronbach’s alpha. Convergent validity was established based on the standardized factor loading and average variance extracted (AVE). Discriminant validity was established using AVE and correlations. The differences between the standardized coefficients of supplier and customer coefficients were then tested against their pooled variance. Results show that suppliers tend to have a higher perception of their delivery on some constructs and customers on some other constructs. Suppliers perceived their product, place, price and process were adequate while customer data showed otherwise. It was promising that promotion, physical evidence, and people showed customer perceptions were more favourable than suppliers’ expectations. Interestingly, customers perceived that the people factor behind the construction industry was excellent. The findings recommend that suppliers scale their perceptions to be closer to the reality perceived by the customers. The study concludes that this approach of evaluating the supplier-customer perceptions is highly beneficial to the supplier.